Cost-effectiveness of human papillomavirus vaccine in China: a systematic review of modelling studies - Haitao Wang; Wenchuan Shi; Xiaoli Cheng; Xiao Zang (BMJ Open)
Objectives China suffers from high burdens of human papillomavirus (HPV) and cervical cancer, whereas the uptake of HPV vaccine remains low. The first Chinese domestic HPV vaccine was released in 2019. However, collective evidence on cost-effectiveness of HPV vaccination in China has yet to be established. We summarised evidence on the cost-effectiveness of HPV vaccine in China.Design Systematic review and narrative synthesisData sources PubMed, EMBASE, China National Knowledge Infrastructure and Wanfang Data were searched through 2 January 2021Eligibility criteria for selecting studies Cost-effectiveness studies using a modelling approach focusing on HPV vaccination interventions in the setting of China were included for review.Data extraction and synthesis We extracted information from the selected studies focusing on cost-effectiveness results of various vaccination programmes, key contextual and methodological factors influencing cost-effectiveness estimates and an assessment of study quality.Results A total of 14 studies were included for review. Considerable heterogeneity was found in terms of the methodologies used, HPV vaccination strategies evaluated and study quality. The reviewed studies generally supported the cost-effectiveness of HPV vaccine in China, although some reached alternative conclusions, particularly when assessed incremental to cervical cancer screening. Cost of vaccination was consistently identified as a key determinant for the cost-effectiveness of HPV vaccination programmes.Conclusions Implementing HPV vaccination programmes should be complemented with expanded cervical cancer screening, while the release of lower-priced domestic vaccine offers more promising potential for initiating public HPV vaccination programmes. Findings of this study contributes important evidence for policies for cervical cancer prevention in China and methodological implications for future modelling efforts.